2019
DOI: 10.1155/2019/7529263
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis on the Effects of Binary Interaction between Typhoons Tembin and Bolaven in 2012

Abstract: e binary interaction is one of the most challenging factors to improve the forecast accuracy of multiple tropical cyclones (TCs) in close vicinity. e effect of binary interaction usually results in anomalous track and variable intensity of TCs. A typical interaction type, one-way influence mode, has been investigated by many studies which mainly focused on the anomalous track and recordbreaking precipitation, such as typhoons Morakot and Goni. In this paper, a typical case of this type, typhoons Tembin and Bol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Many studies have demonstrated that the motion of tropical cyclones has the best correlation with environmental steering flows (Carr & Elsberry, 1990; Chan & Gray, 1982; Xian & Chen, 2019). Figure 11 shows the Western Pacific subtropical high (WPSH, denoted by the characteristic line: 588 dagpm) at 500 hPa and the track of Typhoon Hato.…”
Section: Experimental Study Of Assimilating the Amv Datamentioning
confidence: 99%
“…Many studies have demonstrated that the motion of tropical cyclones has the best correlation with environmental steering flows (Carr & Elsberry, 1990; Chan & Gray, 1982; Xian & Chen, 2019). Figure 11 shows the Western Pacific subtropical high (WPSH, denoted by the characteristic line: 588 dagpm) at 500 hPa and the track of Typhoon Hato.…”
Section: Experimental Study Of Assimilating the Amv Datamentioning
confidence: 99%
“…is study used WRF version 3.6.1 to simulate Typhoon Hato by performing 60 h integrations that were initialized at 1200 UTC on August 21, 2017, and ended at 0000 UTC on August 24, 2017. e initial 12 h period was treated as the model spin-up time. As shown in Figure 1, the simulation incorporated two nested domains: d01 and d02, [32][33][34]; however, no cumulus parameterization scheme was used for domain d02 because updrafts can be resolved sufficiently at 3 km resolution, resulting in explicit convective vertical transport [1]. Long and shortwave radiation was computed using the Rapid Radiative Transfer Model for global climate models [35][36][37].…”
Section: Scheme Description and Experimental Designmentioning
confidence: 99%
“…None of the four experiments included assimilated observational data. Domain d01 used the Kain-Fritsch cumulus parameterization scheme [32][33][34]; however, no cumulus parameterization scheme was used for domain d02 because updrafts can be resolved sufficiently at 3 km resolution, resulting in explicit convective vertical transport [1]. Long and shortwave radiation was computed using the Rapid Radiative Transfer Model for global climate models [35][36][37].…”
Section: Scheme Description and Experimental Designmentioning
confidence: 99%
“…Long and shortwave radiation was computed using the Rapid Radiative Transfer Model for global climate models [35][36][37]. Boundary layer processes were parameterized using the Yonsei University planetary boundary layer scheme [33,36,38]. For the surface layer option, the revised MM5 Monin-Obukhov scheme was selected.…”
Section: Scheme Description and Experimental Designmentioning
confidence: 99%